'Steady Ships' in the COVID-19 Crisis: Australian Public Library Responses to the Pandemic. Issue 2 (3rd April 2021) - Garner, Jane; Hider, Philip; Jamali, Hamid R.; Lymn, Jessie; Mansourian, Yazdan; Randell-Moon, Holly; Wakeling, Simon
ABSTRACT: This paper reports on part one of a multi-part research project investigating Australian public library responses to the requirement to close their physical sites due to the COVID-19 pandemic in 2020. The aim was to examine how Australian public libraries responded to the crisis during their periods of closure in terms of services and resources, the challenges they faced, and the role locality played in their response. In total, 212 public library authority managers completed an online questionnaire survey in August 2020 representing 695 public library branch locations. The results showed that during their periods of closure of their physical sites, libraries established new services (e.g. wellbeing phone calls, delivery of craft kits to users) and expanded several existing ones, especially those related to e-resources. The biggest challenge reported was managing staff working arrangements. While most libraries kept permanent staff and fixed-term staff on full hours, most completely cut volunteers and casual staff hours. There were some geographic differences in the response of libraries to the crisis. Overall, however, whilst metropolitan, regional and remote public libraries faced immense challenges, especially regarding staffing and human resources, they were also able to respond rapidly and with agility to the challenges brought about by COVID-19.